Advancing mechanical design pedagogy with hololens 2 mixed reality environments: a cybergogy exploration - Wan Salihuddin, Wan Muhammad Hafiy; Abdul Aziz, Faieza (ModTech Publishing House, 2024)
Mixed Reality (MR) and Augmented Reality (AR) technologies have gained popularity among companies due to their ability to engage user with digitalized 3D media and information. The ability to interact with the virtual objects while keeping the real-world scenery make them very useful in certain fields. Nowadays, traditional teaching methods, which involve using paper to deliver information and exercises, are outdated. With the advancement of technology, the modernization of teaching process should be utilized to improve the quality of education, especially involving laboratory experiment. Current learning process can be improved in many aspects as traditional method is time-consuming and prone to errors, which affect the result. The goal of this work is to develop an MR application for Programmable Logic Controller (PLC) experiments, evaluate the effectiveness of the developed MR application for the chosen laboratory experiments and implement MR in education system to achieve goal 4 (Quality Education) of Sustainable Development Goal (SDG). Microsoft Hololens 2 and a smartphone were used in this experiment together with a Programmable Logic Controller (PLC) Lab Apparatus. AR and MR application were developed, beginning with modeling 3D in SOLIDWORKS, then transferred to Blender 3.4, Unity 3D, and Vuforia engine. The scripts were then compiled, and the scenes were rendered before the file can be exported into the smart glasses. Thirty (30) participants from Department of Mechanical and Manufacturing Engineering were introduced to MR and AR technologies. This case study collected three main data during the experiment: Task Completion Time (TCT), error counts and number of hints. Participants were also required to answer a set of questionnaires at the end of the experiment. The result showed that 60% of the participants preferred to use MR-based instruction compared to other methods. MR-based instruction also receives good and positive feedback from the questionnaires.